Impact of Graduating with Honors on Entry Wages of Economics Majors - Salim Atay; Gunes A. Asik; Semih Tumen (Institute of Labor Economics (IZA), 2023)
Employers use various proxies to predict the future labor productivity levels of the job applicants. Success in school, especially in high-level coursework, is among the most widely used proxies to screen the entry-level candidates. We estimate the causal effect of graduating with honors – i.e., with a GPA of 3.00 and above out of 4.00 – on the starting wages of economics majors in Türkiye. Using comprehensive micro data on all economics majors between 2014-2018, matched with administrative records about their first jobs, we implement a regression discontinuity analysis to investigate whether there is any statistically significant jump in the starting wages at the honors-degree cutoff. We find that graduating with honors increases the wages of males, while there is no impact on females. We further document that the impact on males is almost entirely driven by the graduates of non-elite universities. In particular, graduating with an honors degree increases the entry wages of males from non-elite universities by about 4 percent, on average. We provide an explanation for these patterns using the theory of statistical discrimination. We discuss the potential reasons behind the heterogeneous signal value of graduating with honors between males versus females and elite versus non-elite university graduates.
Keywords: J31; J71; I26; 330; honors degree; economics majors; entry wages; statistical discrimination; regression discontinuity